ROLE OF FINE NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF SUBCUTANEOUS CYSTICERCOSIS — A REPORT OF 66 CASES - NISHA P MALIK; ASHUTOSH SINGH; VEENA K SHARMA; V .K SHARMA (International Journal of Pharma and Bio Sciences, 2013)
Cysticercosis is caused by larval stage of tape worms Taenia solium (T. solium). Human beings get infected by eating undercooked pork or vegetables and drinking contaminated water infected with eggs of T. solium. Human cysticercosis commonly manifests as subcutaneous and intramuscular nodules. This study highlights the role of fine needle aspiration cytology (FNAC) in the diagnosis of subcutaneous cysticercosis. FNAC was performed using 23/21 gauge needle and 20 ml disposable plastic syringe fitted to a specially designed holder. Total, 66 cases were diagnosed to have cysticercosis, some rare sites were also aspirated like midline neck swelling & breast. In 48 cases (72.72%) actual parasitic structures, like fragment of the wall or tegument of parasite were demonstrated. In rest of cases inflammatory cell and eosinophils were seen. if the FNAC is done by trained cytopathologist with thin needle and with precautions, then it is quite safe and cost effective method, thereby eliminating the need of histopathological examination.